REPETITION AND FANTASY IN SPRING, POEM FOR SOPRANO, CLARINET AND PIANO, BY CARMEN PETRA-BASACOPOL - Şerban MARCU (Studia Universitatis Babeş-Bolyai. Musica)
The present study, part of the research grant The artistic and social impact of the contemporary music of the 21st century from the perspective of the relationship composer-performer-audience (project director Assistant Professor Cristian Bence-Muk, D.Mus.) investigates the structural and rhetoric aspects in the poem Spring, for soprano, clarinet and piano, by Carmen Petra-Basacopol, on the verses of poet Mariana Dumitrescu. The analysis focuses on the relationship between musical techniques (tonal systems, rhythm, timbrality) and the literary text, highlighting the oscillation between rigour (leitmotifs, ostinatos, elements of reprise) and fantasy (improvisational writing – especially for the clarinet –, the madrigal-type discourse).